The organized mind : thinking straight in the age of information overload - Levitin, Daniel J. (New York, N.Y. : Dutton, 2020)
"Daniel J. Levitin, Ph.D., uses the latest brain science to demonstrate how people with "organized" minds excel--and how readers can use their methods to regain a sense of mastery over the way they organize their homes, workplaces, and lives"--OCLC.
Includes bibliographical references and index.
Library Journal
New York Times
Publisher's Weekly
Kirkus Review, July 2014
Library Journal, August 2014
Keywords: Attention; Distraction (Psychology); Orderliness; Time management; Attention; Distraction (Psychology); Orderliness; Time management